Anti‐high mobility group box‐1 monoclonal antibody treatment of brain edema induced by influenza infection and lipopolysaccharide. Issue 7 (31st March 2018) - Nosaka, Nobuyuki; Hatayama, Kazuki; Yamada, Mutsuko; Fujii, Yousuke; Yashiro, Masato; Wake, Hidenori; Tsukahara, Hirokazu; Nishibori, Masahiro; Morishima, Tsuneo
Abstract : Encephalopathy is a major cause of influenza‐associated child death and severe neurological sequelae in Japan, highlighting the urgent need for new therapeutic strategies. In this study, we evaluated the effects of anti‐high mobility group box‐1 monoclonal antibody (α‐HMGB1) treatment on brain edema induced by influenza A virus (IAV) and lipopolysaccharide in 4‐week‐old BALB/c female mice. The results showed that administration of 7.5 mg/kg α‐HMGB1 1 h after IAV (A/Puerto Rico/8/34) inoculation significantly alleviated brain edema at 48 h after IAV inoculation, as confirmed by the suppression of Evans Blue dye leakage and matrix metallopeptidase‐9 mRNA expression in the brain. Moreover, we also observed suppression of oxidative stress and different cytokines in IAV‐inoculated mice. The expression of plasminogen activator inhibitor‐1 was also attenuated following treatment with α‐HMGB1. Notably, α‐HMGB1 treatment had no effect on virus propagation in the lung. In summary, anti‐HMGB1 treatment may improve the prognosis in cases with influenza‐associated encephalopathy by attenuating brain edema and reducing the inflammatory responses induced by HMGB1.